Potential of butterfly pea (Clitoria ternatea) nanoherbal on spermatozoa quality in hyperglycemic rats - Putri, Komala Amelia; Christijanti, Wulan; Marianti, Aditya (Bioeksperimen: Jurnal Penelitian Biologi, 2026)
Hyperglycemia is a condition characterized by elevated blood glucose levels that induce free radical formation, leading to reduced spermatozoa quality. Butterfly pea (Clitoria ternatea) contains antioxidant compounds and is formulated as a nanoherbal to enhance bioavailability. This study aimed to evaluate the potential of butterfly pea nanoherbal in improving spermatozoa quality in hyperglycemic rats. This experimental study employed a post-test only control group design using 25 male Wistar rats divided into a healthy control group and hyperglycemic groups induced by alloxan (125 mg/kg BW). The hyperglycemic groups consisted of a metformin control (400 mg/kg BW) and butterfly pea nanoherbal treatment groups at doses of 12.5, 25, and 50 mg/kg BW administered for 28 days. Data were analyzed using One-Way ANOVA followed by the Least Significant Difference (LSD) post hoc test. The results showed that spermatozoa concentration in the healthy control group differed significantly from the positive control, P1, and P2 groups (p<0.05), but not from the P3 group. Spermatozoa motility and viability also showed significant differences among groups (p<0.05). It can be concluded that butterfly pea flower nanoherbal significantly improves spermatozoa quality in hyperglycemic rats.